2008
DOI: 10.1590/s0102-311x2008000600018
|View full text |Cite
|
Sign up to set email alerts
|

O agente comunitário de saúde no controle da tuberculose: conhecimentos e percepções

Abstract: Este estudo analisa o conhecimento dos agentes comunitários de saúde no controle da tuberculose e a autopercepção do seu nível de conhecimento e de sua importância no enfrentamento da doença, no Município de Vitória, Espírito Santo, Brasil. Tratou-se de um estudo de corte transversal. Um questionário semi-estruturado, auto-aplicável e pré-testado foi preenchido por 105 agentes comunitários de saúde randomicamente selecionados. A comparação das proporções entre os grupos formados pela estratificação por tempo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
28

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
2
9
0
28
Order By: Relevance
“…Um exemplo é a dificuldade na identificação de casos suspeitos de TB, apontando a necessidade de investigações do processo de formação do conhecimento acerca da enfermidade 41 . A fim de abordar o tema especificamente para os agentes, o Ministério da Saúde, em parceria com a Secretaria de Políticas de Saúde, elaborou uma cartilha 42 com o objetivo de orientá-los sobre o tema e mostrar-lhes algumas medidas de controle da doença.…”
Section: Discussionunclassified
“…Um exemplo é a dificuldade na identificação de casos suspeitos de TB, apontando a necessidade de investigações do processo de formação do conhecimento acerca da enfermidade 41 . A fim de abordar o tema especificamente para os agentes, o Ministério da Saúde, em parceria com a Secretaria de Políticas de Saúde, elaborou uma cartilha 42 com o objetivo de orientá-los sobre o tema e mostrar-lhes algumas medidas de controle da doença.…”
Section: Discussionunclassified
“…12 These professionals present special characteristics because they work within the communities where they live and become reference points for the populations of their areas. 8 The reason why only a single study 14 on occupational risks among CHAs was found through surveying the The mean risk found in the two groups was 27.9%. This was similar to the result from Rodrigues et al, 14 who found a prevalence of 26.7% among CHAs in Cachoeiro de Itapemirim, which was signifi cantly greater than their domestic worker controls (3.3%).…”
Section: Discussionmentioning
confidence: 99%
“…20 It allows the CHA to identify, in the community, people who have been coughing for three weeks or more and forward them for a tuberculosis test. 24 When a new tuberculosis case is detected, all contacts are investigated. 25 Another important aspect that should be taken into account is the use of interprofessional teams, with social workers and psychologists, to construct strategies that permit reducing abandonment.…”
Section: Abandonment Associated With Health Service Functioning For Cmentioning
confidence: 99%